Learning Pelvic Anatomy and Pathology Through Drawing: An Interactive Session in the Obstetrics and Gynecology Clerkship - Elisabeth N. Adkins; Elizabeth Barrett; Josette D'Amato; Rose A. Maxwell; Marilyn Kindig (Association of American Medical Colleges, 2023)
Introduction Within undergraduate medical education, there is a gap between students' understanding of anatomy and application of that knowledge within surgical specialties. The integration of drawing, in conjunction with traditional learning, has been shown to increase retention and understanding of information. Currently, no educational curriculum integrates drawing to aid in medical students' understanding of surgical pelvic anatomy. We anticipated that the utilization of drawing anatomy in an OB/GYN clerkship would enhance students' ability to explain surgical pelvic anatomy and pelvic pathology. Methods At the beginning of the OB/GYN clerkship, third-year medical students participated in an interactive, 1.5-hour session requiring them to draw pelvic anatomy, present their work, and explain topics related to pelvic surgery and pathology to the other clerkship students. At the end of their clinical rotation, the students were invited to complete a five-item survey to assess long-term retention and understanding of concepts presented in the session. Frequencies and percentages were calculated for all categorical/ordinal variables to describe survey participants and question responses. Results Thirty-seven of 44 respondents (84%) reported that the anatomy interactive session prepared them for the surgical portion of the OB/GYN clinical rotation. Thirty-five respondents (80%) reported that drawing the pelvic structures helped their understanding of pelvic pathology; 33 respondents (75%) reported they had a thorough understanding of pelvic anatomy after taking the OB/GYN anatomy interactive educational session (p < .001). Discussion Our session shows that integrating drawing and anatomy increases students' ability to discuss pelvic pathology and surgical anatomy.